An experimental study of cavity flow over a 2-D wall-mounted fence in a variable boundary layer. (August 2018) - Barbaca, Luka; Pearce, Bryce W.; Brandner, Paul A.
Highlights: Ventilated and natural cavity flow over a 2-D wall-mounted fence is investigated. The effect of variable fence immersion in the wall boundary layer is determined. A similar cavity topology is observed for ventilated and natural cavity flow. Gas entrainment largely via re-entrant jet, some also via turbulent surface break-up. The dependence of hydrodynamic forces on the investigated parameters is established. Abstract: Ventilated and natural cavity flow over a 2-D wall-mounted fence immersed in a boundary layer is experimentally investigated in a cavitation tunnel. Cavity topology, upstream wall pressure distribution and the resulting hydrodynamic forces were determined as a function of ventilation rate, fence immersion in the oncoming boundary layer and free-stream conditions. Cavities exhibit a typical re-entrant jet behaviour, which is the primary mechanism of air/vapour entrainment into the main flow. Some entrainment is also observed via the turbulent break-up at the cavity surface, the intensity of which increases with deeper immersion of the fence within the wall boundary layer. A similar cavity topology, apart from some difference in the wake, is observed for ventilated and natural cavities at the same flow conditions. This similarity is also present in the relations between all other parameters investigated. It was found that with a decrease in cavitation number lift (i.e. force normal to the wall) increases and drag (i.e. force normal to the fence) decreases, resulting in an increased hydrodynamic efficiency of the wall/fence system. With an increase in fence immersion in the boundary layer, lift and drag both increase at the same rate, resulting in a constant lift-to-drag ratio.